2011
DOI: 10.1007/s12192-010-0242-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide pretreatment protects against ischemia/reperfusion injury via increase of HSP70 and inhibition of NF-κB

Abstract: It has been reported that pretreatment of rats with lipopolysaccharide (LPS) increases myocardial functional recovery in ischemia/reperfusion (I/R) hearts. However, the mechanisms by which LPS induces cardioprotection against I/R injury have not been fully elucidated. In this study, we pretreated rats with LPS (1.0 mg/kg) 24 h before they were subjected to I/R injury, and then examined the roles of heat shock protein-70 (HSP70) and nucleus factor-κB (NF-κB) in LPS-induced cardioprotection. We observed that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…Importantly, the addition of PfHz caused further enhancement of NF-κB translocation into the nucleus, with peak expression at 8 h under physiological (37°C) and heat-shock conditions (42°C, Figures 4A and B). Consistent with the fact that heat-shock treatment increases Hsp70 and thereby reduces NF-κB translocation into the nucleus (20)(21)(22), the effect of PfHz on NF-κB at 42°C was not as pronounced as that observed at 37°C (Figures 4A and B). the time-dependent effect of PfHz on protein levels was determined.…”
Section: Circulating Glutamine Levels In Children With Malariasupporting
confidence: 74%
See 2 more Smart Citations
“…Importantly, the addition of PfHz caused further enhancement of NF-κB translocation into the nucleus, with peak expression at 8 h under physiological (37°C) and heat-shock conditions (42°C, Figures 4A and B). Consistent with the fact that heat-shock treatment increases Hsp70 and thereby reduces NF-κB translocation into the nucleus (20)(21)(22), the effect of PfHz on NF-κB at 42°C was not as pronounced as that observed at 37°C (Figures 4A and B). the time-dependent effect of PfHz on protein levels was determined.…”
Section: Circulating Glutamine Levels In Children With Malariasupporting
confidence: 74%
“…Circulating Aberrant NF-κB activation has been associated with overabundant inflammatory events in arthritis, asthma, ischemia, septic shock and other autoimmune and inflammatory diseases (19,20). Persistent inhibition of NF-κB activation has been linked to apoptosis, inappropriate immune cell development and delayed cell growth (19).…”
Section: Inflammatory Mediator and Glutamine Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be activated by a variety of different stimuli and it participates in expression and regulation of a variety of genes, especially genes involved in defense functions of the body. In recent years, studies have shown that myocardial ischemia at early stage can induce activation of NF-κB to regulate gene transcription (Xiyuan et al, 2009) and NF-κB plays an important role in myocardial ischemic preconditioning, ischemia, hypoxia, reperfusion injury and apoptosis, especially in the process of inducing myocardial inflammatory reaction, and increasing the release of TNF-α, IL-1β and IL-6 (Lu et al, 2009;Yao et al, 2011), and aggravating myocardial injury. At present, a variety of NF-κB inhibitors have been used to relieve myocardial ischemia and reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Both increased production of heat shock proteins and their active participation in the process of wound healing have been demonstrated over a period of approximately two to ten hours after the damage [23,24]. It is known that increased production of hsp70 protein may occur in the case of tissue damage that is caused both by internal tissue factors, such as PHSRN peptide derived from fibronectin [25], and bacterial lipopolysaccharides [26], where hsp70 expression inhibits cytokine excretion induced by lipopolysaccharides; this increases the survival rate of (for example) rats injected with lipopolysaccharides [27].…”
mentioning
confidence: 99%